The subject’s relationship with nutrition: A case study - Fischer Llanos, Angela (2022)
This article deals with the subject's relationship with food, insofar as it is understood that this relationship is not like that of other animals, instinctive, but rather obeys a drive and the satisfaction of a desire. In this sense, a case study is given in which the symptomatology of an anorexic subject is addressed, in which a "desire for nothing" is reported. This characteristic leads the subject to not eat and leads to pernicious weight loss that can culminate in death. What occurs in anorexia is a fault in the imaginary register that dismantles the image itself and makes it unpleasant for the subject: they always look fatter; they always look bad. Psychoanalytic work is proposed as a way to reverse this "desire for nothing" and turn it into a vibrant subjective desire. Psychoanalysis goes beyond the question of making the subject eat, this is undoubtedly very important, but the analytical work aims at the patient discovering in the analyst an object of desire, an unknown X and hooking on it. One of the ways of the cure is that the psychoanalyst finds that the anorexic enjoys his symptom and in this plane the psychoanalyst must try a rewriting of the deadly symptom. The symptom is the way of enjoying the unconscious, as Lacan says, this must be put in evidence in the analytic cure.